The Effectiveness Of Loan Funds At Bank Financial Institutions And Non-Bank Financial Institutions (Study Of BRI And Pegadaian Nunukan Branch) - Sri Astika; Sinaga, Samuel Partogi Hasubungan; Harianti, Harianti; Nurul Aspadilah; Muhammad Syarif (SEAN Institute, 2024)
The presence of bank financial institutions and non-bank financial institutions means that people have many alternative choices of providers of financial capital. The community is given freedom and flexibility in determining financial institutions that suit their needs and capabilities in repaying loan funds to help with financial needs. This was utilized by BRI and Pegadaian Nunukan. This research aims to determine the mechanism for lending funds to BRI and Pegadaian Nunukan Branch, and to determine the effectiveness of lending funds between BRI and Pegadaian Nunukan Branch. This research is qualitative research, using observation, interviews and documentation as data collection methods. The data obtained was then compared using descriptive comparative methods. The results of this research can be concluded that BRI and Pegadaian Nunukan Branch have their respective advantages. Pegadaian has the advantage of lower interest and fines compared to BRI. Meanwhile, BRI has the advantage of a larger loan limit, namely up to 50 million, can be repaid in a maximum of 5 years and without using collateral. If a customer wants to apply for a loan of 10 million or less, the Nunukan Branch Pegadaian will be more effective for borrowing funds because the interest at the Nunukan Branch Pegadaian is lower compared to the BRI Nunukan Branch. Apart from interest, the fines charged if customers are late in paying installments are also lower than BRI Nunukan Branch.